The Malthusian Paradox: performance in an alternate reality game - Evans, Elizabeth; Flintham, Martin; Martindale, Sarah (Springer, 2014)
The Malthusian Paradox is a transmedia alternate reality game (ARG) created by artists Dominic Shaw and Adam Sporne played by 300 participants over three months. We explore the design of the game, which cast players as agents of a radical organisation attempting to uncover the truth behind a kidnapping and a sinister biotech corporation, and highlight how it redefined performative frames by blurring conventional performer and spectator roles in sometimes discomforting ways. Players participated in the game via a broad spectrum of interaction channels, including performative group spectacles and 1-to-1 engagements with game characters in public settings, making use of low- and high-tech physical and online artefacts including bespoke and third party websites. Players and game characters communicated via telephony and social media in both a designed and an ad-hoc manner. We reflect on the production and orchestration of the game, including the dynamic nature of the strong episodic narrative driven by professionally produced short films that attempted to respond to the actions of players; and the difficulty of designing for engagement across hybrid and temporally expansive performance space. We suggest that an ARG whose boundaries are necessarily unclear affords rich and emergent, but potentially unsanctioned and uncontrolled, opportunities for interactive performance, which raises significant challenges for design.